(untitled) (Research, Society and Development, 2023)
Alopecia Areata (AA) is a pathology that affects the follicular unit and nail changes concomitantly with the condition, with an undefined and multifactorial cause and evident autoimmune and genetic manifestations. Therefore, the objective is to evaluate the use of corticosteroids in the treatment of Alopecia Arreata. This is a methodical literature review, with the proposal to carry out a search for scientific articles through electronic research, based on the data listed: SCIELO (Online Scientific Electronic Library) Lilacs (Latin American and Caribbean Literature in Health Sciences), Bireme (Latin American and Caribbean Center on Health Sciences Information), Pubmed (Search platform of the National Library of Medicine), between the years 2010 to 2022. In the results, the safety and efficacy of corticosteroids for patients affected by AA proved to be responsive and safe. In the selected studies, it was understood that this drug has as a mechanism of action there is the stimulation of hair folic acid, thus increasing the duration of its anagen phase.